Diversity, composition, and structure of wood species of tropical dry forest in Lerma, Campeche - Zamora-Crescencio, Pedro; Aragón-Gastélum, José Luis; Vargas Contreras, Jorge Albino; Barrientos-Medina, Roberto Carlos; Aguirre-Crespo, Francisco Javier; Gutiérrez-Báez, Celso; Plasencia-Vázquez, Alexis Herminio (Ecosistemas y Recursos Agropecuarios, 2024)
The objective of this study was to describe the diversity, composition, and structure of the woody vegetation in a section of LDF in Lerma, Campeche. Between August and September 2018, 10 plots of 10 × 10 m2 (1 000 m2 in total) were delimited, measuring all woody individuals with diameter at breast height (DBH = 1.30 cm). The structure of the site was described based on the relative values of density, frequency, and dominance (IVI), as well as the distribution of diameter classes. Diversity was estimated with the Shannon-Wiener index (H'), while equity was measured by the Pielou index. 40 woody species were recorded, belonging to 35 genera and 19 families. The H' index had a value of 2.92, and the Pielou index was 0.79, the density was 8 950 ind ha-1. Gymnopodium floribundum (204 individuals) and Lonchocarpus xuul (129) were the most abundant species. Bursera simaruba and Lysiloma latisiliquum showed higher diameter values (36 and 28.6 cm DBH, respectively). The families Rubiaceae (eight species), Fabaceae (five species), Ebenaceae and Polygonaceae (three species each) were the most representative. The species with the highest IVI were Gymnopodium floribundum (48.24%), Lonchocarpus xuul (29.12%), Bursera simaruba (26.11%) and Lysiloma latisiliquum (24.98%), these species being the most important in the structure of the LDF in the site. The distribution of the diameter classes suggests that the section of the LDF in Lerma Campeche is in an adequate state of regeneration.
Keywords: Floristic Composition; Importance Value Index; Floristic Richness; Vegetation